Behavioral analysis of a solitary individual of Pontoporia blainvillei (Cetacea: 1 Pontoporiidae) in the Port channel of Santos, SP - Grellet, Gabriel Mendonça [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
The present study aimed to analyze the behavior of a solitary specimen of Pontoporia blainvillei, a cryptic endangered species of odontocete, in an atypical occurance in the port channel of Santos (SP, Brazil), through an ethological approach to describe behavioral states and events, as well as to evaluate its sociability stages. An ethogram was prepared based on behaviors previously recorded for the species and members of the Delphinidae family. The focal-animal sampling was applied to the analysis of 321 selected videos — from a total of 610 opportunistic records obtained between July 2021 and April 2022 —, totaling 1,197 minutes of observations. The videos had an average length of 3:22 minutes. The total surface time recorded was 98.6 minutes, with an average of eight seconds per video. The most recurrent behavioral state was “Seek Human Interaction” (n=114), corresponding to 62.3% of the total surface time. 49 of the 123 behavioral events described by Müller (1998) were identified, with diving (n=1,218), breathing (n=344); and swimming (n=338) being the most frequent categories. Thus, some unusual categories to the species, such as head movements (n=133) and aerial behaviours (n=62) should also be highlighted. After a possible agonistic interaction with antropogenic gear on September 2021, the state to “Seek Human Interaction” ceased, as of its observed behavioral repertoire decreased along. This is an unprecedented and rare case for the species, since the individual underwent a regression in the sociability stages proposed for solitary-sociable dolphins. Despite this case refers to na outlier individual, the findings presented here provide relevant subsidies for future monitoring, rehabilitation, and conservation actions of franciscanas.

O presente estudo teve como objetivo analisar o comportamento de um espécime solitário de Pontoporia blainvillei, espécie críptica de odontoceto ameaçada de extinção, observado de forma atípica no canal portuário de Santos (SP), por meio de ferramentas etológicas para descrição de estados e eventos comportamentais, bem como à avaliação de estágios de sociabilidade. Para isso, foi elaborado um etograma com base em comportamentos previamenteregistrados para a espécie e membros da família Delphinidae. A metodologia adotada consistiu na técnica de animal-focal, aplicada à análise de 321 vídeos selecionados — a partir de um total de 610 registros oportunísticos obtidos entre julho de 2021 e abril de 2022 —, totalizando 1.197 minutos de observações. Os vídeos tinham em média 3:22 minutos. O tempo total de permanência do animal na superfície foi de 98,6 minutos, com média de oito segundos por vídeo. O estado comportamental mais recorrente foi “Buscando Interação” (n=114), correspondendo a 62,3% do tempo total de superfície. Foram identificados 49 dos 123 eventos comportamentais descritos por Müller (1998), sendo os comportamentos de mergulhos (n=1.218), respirações (n=344); e nados (n=338) aqueles que apresentaram maior frequência numérica. Com destaque a comportamentos incomuns à espécie, como movimentação de cabeça (n=133) e comportamentos aéreos (n=62). A partir de setembro, após possível interação negativa com petrechos antrópicos, constatou-se a cessão do estado “Buscando Interação” e uma redução de seu repertório comportamental observado. Trata-se de um caso inédito e raro para a espécie uma vez que o espécime passou por uma regressão nos estágios de sociabilidade, mas que, apesar de se referir a uma situação excepcional, os achados apresentados fornecem subsídios relevantes para futuras ações de monitoramento, reabilitação e conservação das toninhas.
Análise comportamental de um indivíduo solitário de Pontoporia blainvillei (Cetacea: Pontoporiidae) no canal do Porto de Santos, SP
Keywords: Cetáceos; Toninhas; Ecologia; Comportamento